Increased Angiogenesis and Lymphangiogenesis in Metastatic Sentinel Lymph Nodes Is Associated With Nonsentinel Lymph Node Involvement and Distant Metastasis in Patients With Melanoma. (May 2016) - Pastushenko, Ievgenia; Van den Eynden, Gert G.; Vicente-Arregui, Sandra; Prieto-Torres, Lucia; Alvarez-Alegret, Ramiro; Querol, Ignacio; Dirix, Luc Y.; Carapeto, Francisco J.; Vermeulen, Peter B.; Van Laere, Steven J.
Abstract : Abstract: Lymph node angio- and lymphangio-genesis have been shown to play an important role in the premetastatic niche of sentinel lymph nodes. In the current study we have investigated the association of angio- and lympangio-genesis related parameters in metastatic sentinel lymph nodes of patients with melanoma with the presence of nonsentinel and distant organ metastasis. Peritumoral and intratumoral relative blood and lymphatic vessel areas (evaluated by Chalkley method), blood and lymphatic microvessel densities, and the rates of blood and lymphatic vessel proliferation were assessed in primary tumors and sentinel lymph node metastasis of 44 patients with melanoma using CD34/Ki-67 and D240/Ki-67 immunohistochemical double staining. Primary melanoma exhibited significantly higher rate of lymphatic proliferation compared with its lymph node metastasis ( P < 0.05), while lymph node metastasis showed significantly higher rate of blood vessel proliferation ( P < 0.05). Using multivariate logistic regression model, the rate of peritumoral lymphatic proliferation was inversely associated with positive nonsentinel lymph node status ( P < 0.05), whereas the rate of intratumoral blood vessel proliferation was associated with distant organ metastasis ( P < 0.05). Using multivariate Cox regression analysis, the rate of intratumoral blood vessel proliferation was also inversely associated with overall survival of patients with melanoma ( P < 0.05).